PCR detection of Mycobacterium paratuberculosis in Crohn's disease granulomas isolated by laser capture microdissection. Issue 5 (1st November 2002) - Ryan, P; Bennett, M W; Aarons, S; Lee, G; Collins, J K; O'Sullivan, G C; O'Connell, J; Shanahan, F
Abstract : Background and aims: The uncertainty surrounding the role of Mycobacterium avium subsp paratuberculosis (Map) in Crohn's disease has been compounded by possible contamination from Map present in the lumen microflora. This study used laser capture microdissection (LCM) and polymerase chain reaction (PCR) to detect Map DNA in subepithelial granulomas, isolated from 15 surgically resected, formalin fixed specimens of granulomatous Crohn's disease and from 12 granulomatous disease controls (10 bowel, 2 non-bowel). Methods: The effect of amplicon size on reliability of PCR from formalin fixed samples was examined by amplifying 435 bp and 133 bp sequences of the human APC gene. After this, nested primers were designed to detect a small fragment (155 bp) of the Map specific IS900 gene in Crohn's granulomas. LCM isolated granulomas from Map culture positive bovine intestine was used as positive control. PCR product specificity was confirmed by direct DNA sequencing. Results: The smaller, but not the larger, fragment of the APC gene amplified reliably in all samples. Amplification of the 155 bp fragment of the IS900 gene detected Map DNA in microdissected Crohn's granulomas in 6 of 15 cases, and in 0 of 12 disease control granulomas. Conclusions: LCM can be used to detect Map DNA in granulomas in a proportion of patients with Crohn's disease. However, formalin fixation requires that comparatively short DNA fragments of the Map specific IS900 gene be targeted, to permit consistent detection. Detection of Map DNA within granulomas might suggest an infectious aetiology in a subset of patients; alternatively, a transmissible agent may not be involved but mycobacterial DNA may influence pathogenesis by modifying the local cytokine responses.